STUDI MOLECULAR DOCKING SENYAWA TURUNAN AURON SEBAGAI INHIBITOR GLIKOPROTEIN SPIKE SARS-COV-2 - Allo, Veliyana Londong; Rahmah, Siti; Gunawan, Rahmat (Akta Kimia Indonesia, 2023)
The spike glycoprotein plays a role in binding and inserting viruses into host cells in the human body. Auron-derived natural compounds are believed to be potential inhibitors of spike glycoprotein. In this study, redocking of the native NAG ligand was carried out, as well as molecular docking of the 6VSB spike glycoprotein viral protein. The bond energy value for redocking the native NAG ligand is -6.2 kcal/mol, and the bond energy value for molecular docking of auron derivative compounds is -7.8 to -7.3 kcal/mol. Based on the bond energy value, the compound with potential as an inhibitor of spike glycoproteins is the 3',4, 4',6-tetrahydroxy auron compound. This is supported by the bond energy value and number of hydrogen bonds for this compound of -7.8 kcal/mol, forming four hydrogen bonds.